A Single-Cell Transcriptome Atlas of the Human Retinal Pigment Epithelium - Xu, Zongren; Liao, Xingyun; Li, Na; Zhou, Hongxiu; Li, Hong; Zhang, Qi; Hu, Ke; Yang, Peizeng; Hou, Shengping (Frontiers in Cell and Developmental Biology, 2021)
Human retinal pigment epithelium (hRPE) cells are arranged in a monolayer that plays an important supporting role in the retina. Although the heterogeneity of specific retinal cells has been well studied, the diversity of hRPE cells has not been reported. Here, we performed single-cell RNA sequencing on 9,302 hRPE cells from 3 donors and profiled a transcriptome atlas. Our results identified two subpopulations that exhibit substantial differences in gene expression patterns and functions. One of the clusters specifically expressed ID3, a macular RPE marker. The other cluster highly expressed CRYAB, a peripheral RPE marker. Additionally, the genes associated with oxidative stress and endoplasmic reticulum stress were more enriched in the macular RPE; the genes related to light perception, oxidative stress and lipid metabolism were more enriched in the peripheral RPE. Additionally, we provided a map of disease-related genes in the hRPE and highlighted the importance of the macular RPE and peripheral RPE clusters P4 and P6 as potential therapeutic targets for retinal diseases. Our study provides a transcriptional landscape for the human retinal pigment epithelium that is critical to understanding retinal biology and disease.